The Role of Sharia Financial Institutions in Improving the Indonesian Economy: Focus on Murabahah Financing - Iin Saputra; Muhammad Aris; Yudi Yudi; Ayub Rangkuti; Nanda Suryadi (Yayasan Pendidikan Islam Al-Matani, 2024)
This research is a literature study that examines the role of sharia financial institutions in improving the Indonesian economy with a focus on murabahah financing. The methodology used involves in-depth analysis of existing literature to produce a solid understanding of how Islamic financial institutions can contribute to the economy through murabahah financing. This study relies on relevant secondary data and literature analysis to provide a meaningful contribution to academic and policy-related understanding. The research results show that the implementation of murabahah financing by sharia financial institutions provides financial solutions in accordance with sharia principles, helps people own interest-free homes, and increases bank profitability and liquidity. Apart from that, murabahah financing also helps sharia financial institutions attract more customers and increase public trust in sharia-based financial services. It also plays a role in supporting financial inclusion, especially for communities that are underserved by conventional financial institutions. Overall, murabahah financing not only provides direct benefits for customers and banks, but also contributes positively to economic growth and welfare of Indonesian society.